A versatile ring trap for quantum gases. (25th June 2021) - de Goër de Herve, Mathieu; Guo, Yanliang; De Rossi, Camilla; Kumar, Avinash; Badr, Thomas; Dubessy, Romain; Longchambon, Laurent; Perrin, Hélène
Abstract: We report on the confinement of a Bose–Einstein condensate in an annular trap with widely tunable parameters. The trap relies on a combination of magnetic, optical and radio-frequency fields. The loading procedure is discussed. We present annular traps with radii adjusted between 20 and 150 μ m. We demonstrate the preparation of persistent flows both with a rotating laser stirrer and with a global quadrupole deformation of the ring. Our setup is well adapted for the study of superfluid dynamics.